Kajian Kitab At-Thabaqat Al-Kubra Karya Ibnu Sa’ad - Anis Tilawati (SINDA: Comprehensive Journal of Islamic Social Studies, 2022)
This article examines the oldest book that has reached the hands of Muslims today, which contains biographies of the narrators of Hadith. The book known as the book of Ath-Thabaqat Al-Kubra was written by Ibn Sa'ad which is certainly not a foreign name for Hadith experts. The researcher in this case tries to examine the book in terms of the author's biography, writing method, characteristics, uniqueness, advantages and disadvantages. The method used is a literature review with qualitative research from several sources in various literatures related to the theme raised. The findings that make this paper new is that the book Ath-Thabaqat Al-Kubra is one of the works in the field of Asma' ar-Rijal which contains the biographical notes of the most important narrators at the most important period in the history of hadith. It is a very rich source from various perspectives, containing very valuable information about the history of Islam. It is described not only as the most important major work in the field, but also in Arabic literature in general.